2018
DOI: 10.1097/iae.0000000000001749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Macular Ischemia in Eyes With Central Retinal Vein Occlusion

Abstract: Optical coherence tomography angiography is a novel technique that enables segmented evaluation of the macular perfusion status in eyes with central retinal vein occlusion and provides visual prognostic information. Enlargement of the macular NPA in the superficial and deep layers was significantly correlated with impaired visual acuity and with decreased macular sensitivity in patients with aflibercept-treated central retinal vein occlusion and resolved macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Several reports [8, 9] have been published recently that evaluate the relationship between macular ischemia and visual function using OCT, OCTA, and microperimetry in eyes with RVO. However, the relationship between retinal ischemia and ME or MA was not examined, and the thickness of the entire retina was measured, not of each retinal layer.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports [8, 9] have been published recently that evaluate the relationship between macular ischemia and visual function using OCT, OCTA, and microperimetry in eyes with RVO. However, the relationship between retinal ischemia and ME or MA was not examined, and the thickness of the entire retina was measured, not of each retinal layer.…”
Section: Introductionmentioning
confidence: 99%
“…Kadomoto et al analyzed RVO patients and showed that visual acuity was associated with the defect length of the foveal EZ band. Macular sensitivity assessed by microperimetry was found to be correlated with the length of EZ disruption [24]. Correlation between visual acuity and EZ disruption was also found in diabetic eyes [4].…”
Section: Plos Onementioning
confidence: 74%
“…7,9,10 Compared to the older imaging modalities, optical coherence tomography (OCT) and OCT angiography (OCTA) enable detailed evaluation of the retinal vasculature parallel or perpendicular to the retinal plane. [11][12][13][14][15][16][17][18][19][20][21] Our recent investigations using OCT 22 or OCTA 14 have indicated that BRVO caused by venous overcrossing might be more prevalent than previously reported and that these cases involve more highly narrowed veins at the causative crossings and a larger retinal non-perfusion area than cases caused by arterial overcrossing. However, the viewing angle of OCT and OCTA used in these investigations might not have been sufficiently large to allow evaluation of retinal vasculature other than at causative crossings.…”
mentioning
confidence: 84%